2019
DOI: 10.31965/dtj.v1i2.452
|View full text |Cite
|
Sign up to set email alerts
|

Peran Orang Tua dalam Pemeliharaan Kesehatan Gigi dan Mulut

Abstract: The Role of Parents in the Maintenance of Dental and Mouth Health. Dental health education must be introduced as early as possible to children so they can know how to maintain oral and dental health properly. The active role of parents in the development of children is very necessary when they are still under preschool age. The active role of parents in question is to guide, provide understanding, remind, and provide facilities to children. Preschoolers cannot maintain their health properly and effectively, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
2
0
5
Order By: Relevance
“…Def-t assessment is calculated per tooth, meaning that if one tooth has more than one caries, for example, there is proximal and buccal caries, the caries will still be counted as one. 13,14 The results showed that most of the students had a very high def-t index (52%). A very high def-t index is a bad condition, because it indicates there are many carious teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Def-t assessment is calculated per tooth, meaning that if one tooth has more than one caries, for example, there is proximal and buccal caries, the caries will still be counted as one. 13,14 The results showed that most of the students had a very high def-t index (52%). A very high def-t index is a bad condition, because it indicates there are many carious teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Mulut yang sehat berarti bebas dari kanker tenggorokan, infeksi dan sariawan, gusi, rangka gigi, gigi tanggal dan penyakit lainnya, sehingga tidak ada gangguan dan membatasi kesejahteraan psikososial kesehatan mulutnya [3].…”
Section: Pendahuluanunclassified
“…Anak usia sekolah dasar tergolong kedalam kelompok rawan penyakit gigi dan mulut (Manbait, et al, 2019). Untuk meningkatkan kesehatan gigi dan mulut, pemerintah melalui Departemen Kesehatan telah melakukan berbagai upaya pendekatan pelayanan kesehatan,yaitu promotif,preventif,kuratif dan rehabilitatif secara terpadu dan berkesinambungan (Herijulianti et al, 2002).…”
Section: Pendahuluanunclassified